Tingkat Densitas Populasi Maggot Pada Media Yang Berbeda - Prana Hartami; Sri Nanda Rizki; Erlangga Erlangga (Fakultas Perikanan dan Kelautan, Universitas Riau, 2015)
Aims research to know the best substrat type for increasing the density of the maggot population. This research was conducted on December 23rd to January 22nd, 2014, at Hatchery and Aquaculture Technology laboratory Cunda, Lhokseumawe. Experimental methods was Complete Random design (CDR) non factorial with 5 treatments and 3 replication. The results showed the best treatment with combination of dregs tofu, dregs coconuts, bran and pal oilcake with the average value of the density of population of maggot 4.60 ind/cm3, weights 190 grams, and a length of 1 cm. Experimental needs to be done further Suggestions to look at other types of media to increased the population density of the maggot.